Possession music of the Shangana-Tsonga - Johnston, Thomas F. (International Library of African Music, 1971)
Exorcism {mancomane) is one of the more important musical practices among the Tsonga of Mozambique and the northern Transvaal, involving possession dancing, playing of the special ncomane tambourine, from which the rite obtains its name, and the singing of spirit-specific songs. It is organised by a specialist diviner or exorcist known as the dzwavi, who is 'licensed' by the chief in return for payment, rather than appointed. Fees known as the mbulaxifuva are collected from patients; this term means 'medicine- pouch loosener', and the fee may be paid in beer, fowl or cash. Successful and well- attended exorcism rites thus tend to be a source of revenue for Tsonga chiefs (through diviners), and the participants and audiences which are attracted into the area provide part of the broad pyramid base necessary to maintain chiefly power and prestige
Keywords: South Africa; Music; Tsonga (African people); Rites and ceremonies; Ethnomusicology; Exorcism; Mozambique; Shangana; African Music